A Study on the Effect of Organic, Inorganic, and Biofertilizers Application on Soil Characteristics and on the Growth of Brassica juncea L. - Narka, I Wayan; Merit, I Nyoman (Journal of Food Security and Agriculture; Vol 1 No 1 (2017): Journal of Food Security and Agriculture, 2017)
A glasshouse scale experiment on the effect of organic, unorganic fertilizer and biofertilizer on growth of Brassica juncea L was conducted at the Faculty of Agriculture, Udayana University. A Randomized Block Design with 8 treatments ( P0: without fertilizer P1: organic fertilizer P2: anorganic fertilizer (N, P, K), P3: biofertilizer (nitrobacter TJ), P4 : P1+P2, P5 :P1+P3, P6: P2+P3, and P7: P1+P2+P3) and triplicate per treatment were  applied in the  experiment. Parameters measured as growth indication included plant height, number of plants, number of leaves, as well as wet and dry weight of the plants. The results showed that application of fertilizer types significantly (p<0.05% or 0.01%) affected all growth parameters of green mustard (Brassica juncea L). The highest dry weight was observed in the treatment of P7 (where the dry weight in this treatment was 344.8% higher than that observed in control (P0)). Treatments of P3, P5, P6, P2, P4, and P1 was found to have dry weight of 258,6%, 203.5%, 200,0%, 96.6%, 89.7%, 31.0% higher than that of control. Types of fertilizers also significantly affected soil properties, such as organic C and N content.